SISTEM INFORMASI PENJUALAN DAN PEMBELIAN OBAT PADA APOTEK DIKA FARMA PONTIANAK BERBASIS WEB - Anna Anna (Jurnal Informatika Kaputama (JIK), 2021)
ABSTRACT Pharmacies play a very important role in health services. Pharmacy as a form of business that has a high complexity also requires an information system in its business activities. All forms of recording, starting from recording incoming drug data, purchasing transactions, selling, searching for drug data and checking stocks to making reports are still done manually. This designed system aims to produce a drug sales and purchase information system at a web-based pharmacy in which it is integrated with an expired drug notification system, computerized recording of sales and purchase transactions, purchase and sales reports, assisting drug data management, and providing information to the public. regarding the availability of stock and the price of the drug sought at the Dika Farma Pontianak Pharmacy only through the web. This application is made using the stages of the Waterfall model which can produce data that is easily accessible, accurate, and fast in the report generation process.